Intercultural Communication Between Topogaro Village Community and Ethnic Chinese Employees in Morowali Regency - Fadhliah; Sitti Murni Kaddi; Stepanus Bodo; Donal Adrian; Nurliana; Selviana (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The purpose of this study is to identify convergence behavior in intercultural communication carried out by Chinese ethnic Chinese employees with local people in Topogaro Village in Morowali Regency. The research method uses qualitative with a case study approach. The informant selection technique uses purposive. Data Collection Techniques are in-depth interviews and direct observation. For analysis techniques using Data Reduction, Data Display and Conlusion Drawing/Verification. The results showed that the intercultural communication process between local people of Topogaro Village and ethnic Chinese Chinese employees in Morowali Regency was marked by convergence behavior such as ethnic Chinese Chinese trying to learn Indonesian, learning about the cultural behavior of local people starting from food and things not to do. From food and things that should not be done. This learning process is basically to be able to establish social interactions with the Topogaro community in Morowali Regency. Convergence or adjustment behavior is basically more done by ethnic Chinese Chinese as a minority community who come to work in one of the private companies in Topogaro Village, Morowali Regency.